A New Look at Judicial Impact: Attorneys' Fees in Securities Class Actions After Goldberger v. Integrated Resources, Inc. - Theodore Eisenberg; Geoffrey P. Miller; Michael A. Perino (Washington University Journal of Law & Policy, 2009)
This Essay attempts to address three questions in the extant judicial impact literature. First, the existing studies use rather insensitive measures of compliance and thus may fail to identify instances of subtle resistance to higher court rulings. A second limitation in the judicial impact literature lies in its restrained focus. Judicial politics in general and the judicial impact literature in particular tend to have a “high court” bias. Also, scholars studying judicial politics less frequently examine the ultimate consumers of judicial policies—the members of society who are subject to the rule the court has announced.
Keywords: Judicial process; Class action lawsuits; Lawyers& #x27; fees; Judicial decision-making; Judicial impact literature